Centres out there?: facets of subregional identities in Orissa - Kulke, Hermann; Berkemer, Georg (Studies in Orissan society, culture and history, 2011)
Contributed articles presented at the fourth Salzau conference in 2003
Keywords: Odisha (India) -- History -- Congresses; Odisha (India) -- Religious life and customs -- Congresses; Aufsatzsammlung; Regionale Identität; Religion; König; Peripherie; Zentrum; Odisha